2009
DOI: 10.1210/jc.2009-0162
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Stimulated Translocation of Glucose Transporter (GLUT) 12 Parallels That of GLUT4 in Normal Muscle

Abstract: Insulin causes GLUT12 to translocate from an intracellular location to the plasma membrane in normal human skeletal muscle. Translocation of GLUT12 in cultured myoblasts was dependent on activation of PI3-K. GLUT12 may have evolutionarily preceded GLUT4 and now provides redundancy to the dominant GLUT4 system in muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 23 publications
1
93
0
1
Order By: Relevance
“…Phosphoinositide 3-kinase (PI3K) activity in the lysates was evaluated using a PI3K ELISA kit (K1000; Echelon Biosciences, Salt Lake City, UT, USA). The plasma membrane of the muscle was obtained as in Stuart et al [15] and checked by cadherin.…”
Section: Methodsmentioning
confidence: 99%
“…Phosphoinositide 3-kinase (PI3K) activity in the lysates was evaluated using a PI3K ELISA kit (K1000; Echelon Biosciences, Salt Lake City, UT, USA). The plasma membrane of the muscle was obtained as in Stuart et al [15] and checked by cadherin.…”
Section: Methodsmentioning
confidence: 99%
“…In the blastocyst-stage embryo GLUT8 translocates to the cell surface in response to insulin and mediates insulin stimulated glucose uptake [83]. Additionally, recent data suggests that GLUT12 may also function as an insulin sensitive glucose transporter [84,85]. It is unknown if GLUT8 or GLUT12 function in the oocyte or cumulus cells.…”
Section: Glucosementioning
confidence: 99%
“…In another study, it has been shown a protein expression ratio for GLUT4: GLU12 of 8:1, representing for GLUT12 around 12 % of the potentially insulin translocable GLUT. Moreover, activation of PI3-K was involved in GLUT12 translocation, as has been described for GLUT4 [32].…”
Section: Physiological Rolementioning
confidence: 52%
“…This physiological function was demonstrated in normal human skeletal muscle, where it was described that GLUT12 is translocated to the plasma membrane together with GLUT4 in response to insulin [32]. This fact was recently confirmed in a GLUT12 over-expressing mice, where the whole body insulin sensitivity and the glucose clearance rate in insulin sensitive tissues was higher than in control mice [26].…”
Section: Physiological Rolementioning
confidence: 68%
See 1 more Smart Citation